Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability. Issue 6 (5th September 2017) - Sherley, Richard B.; Botha, Philna; Underhill, Les G.; Ryan, Peter G.; van Zyl, Danie; Cockcroft, Andrew C.; Crawford, Robert J.M.; Dyer, Bruce M.; Cook, Timothée R.
Abstract: Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant (Phalacrocorax neglectus), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster (Jasus lalandii). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.